2021
DOI: 10.1371/journal.pntd.0009338
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of soil transmitted helminths and risk analysis of hookworm infections in the community: Results from the DeWorm3 Trial in southern India

Abstract: Since 2015, India has coordinated the largest school-based deworming program globally, targeting soil-transmitted helminths (STH) in ~250 million children aged 1 to 19 years twice yearly. Despite substantial progress in reduction of morbidity associated with STH, reinfection rates in endemic communities remain high. We conducted a community based parasitological survey in Tamil Nadu as part of the DeWorm3 Project—a cluster-randomised trial evaluating the feasibility of interrupting STH transmission at three ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…Here we also found that household heads who possessed unimproved toilet facilities were two times more likely to be infected with STHs as compared to household heads who possessed improved toilet facilities. This has also been described in the study conducted in western Cameron and southern India [ 51 , 56 ].…”
Section: Discussionsupporting
confidence: 77%
“…Here we also found that household heads who possessed unimproved toilet facilities were two times more likely to be infected with STHs as compared to household heads who possessed improved toilet facilities. This has also been described in the study conducted in western Cameron and southern India [ 51 , 56 ].…”
Section: Discussionsupporting
confidence: 77%
“…CDDs reported that adult populations in their communities have STH infections, and some of them believed that STH might not be eliminated because not all in their communities were following safe sanitation practices. Studies conducted in the same areas where the CDDs resided showed low levels of improved sanitation facilities (34.6%) and 25.1% unweighted STH prevalence among adults ( 29 ). The FGDs with community women and men from the same communities also showed that adults had STH infections, and that embarrassment associated with having STH prevented them from seeking treatment ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Annual enumeration of the study site carried out between October and December 2019 showed a study population of 147,570 people residing in 38,115 households. Further sociodemographic details on the study site and population in India have also been published (27,29). subsequent round for a total of six trainings.…”
Section: Study Settingmentioning
confidence: 99%
“…The wealth index was assessed using quintiles (1 being low and 5 being high), derived from household assets using principal component analysis as described elsewhere. 18 The outcome variables assessed included the procurement of loans and/or assets sold, and the employment status of individuals in the household during the lockdown, using independent multivariate models. Univariable logistic regression for each of the outcome variables was performed, and significant variables ( P < 0.05) were included in the multivariable logistic regression using backward elimination.…”
Section: Methodsmentioning
confidence: 99%